2021
DOI: 10.3390/ijms22147304
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Composites Reinforced with Walnut Shell Filler Treated with Perlite, Montmorillonite and Halloysite

Abstract: In the following study, polyurethane (PUR) composites were modified with 2 wt.% of walnut shell filler modified with selected mineral compounds–perlite, montmorillonite, and halloysite. The impact of modified walnut shell fillers on selected properties of PUR composites, such as rheological properties (dynamic viscosity, foaming behavior), mechanical properties (compressive strength, flexural strength, impact strength), dynamic-mechanical behavior (glass transition temperature, storage modulus), insulation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Due to the alignment of the fibers, when RPUF is rising, cells’ elongations are expected, especially when the filler is used above the matrix saturation (i.e., those CF 1). Furthermore, the changing of the cells’ mechanism formation, from homogenous to heterogonous, contribute to the overall distribution and lower uniformity of the RPUF cells’ structure [ 47 ], highlighting, again, those CF 1.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the alignment of the fibers, when RPUF is rising, cells’ elongations are expected, especially when the filler is used above the matrix saturation (i.e., those CF 1). Furthermore, the changing of the cells’ mechanism formation, from homogenous to heterogonous, contribute to the overall distribution and lower uniformity of the RPUF cells’ structure [ 47 ], highlighting, again, those CF 1.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, the use of various types of nanofillers such as: fume silica [ 16 ], cellulose nanocrystals [ 17 ], spherical TiO 2 , platelet nanoclay, rod-shaped carbon nanofibers [ 18 ], montmorillonite [ 19 ] and others should be considered as promising solutions in this field. They act as nucleation sites and thus reduce the cell size and, as a result, effectively increase the mechanical properties, fire resistance and thermal stability and reduce the thermal conductivity of PUR foams [ 13 , 20 ]. However, a significant problem with the use of such fillers is their relatively high price and their tendency to agglomerate, which in consequence disturbs the foaming process and deteriorates the properties of the finished foam.…”
Section: Introductionmentioning
confidence: 99%
“…The studies carried out so far show that agricultural waste is a material with high application potential in the production of composite PUR foams. It has been shown that waste products such as buckwheat husks [ 7 ], walnut shells [ 12 , 20 ], plum stones [ 22 ], straw fibre [ 24 ], hemp fibre [ 25 ], wheat slops [ 26 ], rapeseed cake [ 21 ], soy and potato protein [ 27 , 28 ], sugar beet pulp [ 15 ], egg shell [ 29 ], ground coffee [ 30 ], keratin chicken feathers [ 31 ] and many others have a beneficial effect on the properties of foams. Another source of naturally derived fillers is the timber industry.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their properties, HNTs can be used in many fields [ 25 , 26 , 27 , 28 , 29 , 30 ]. The possibility to encapsulate active molecules within their lumen has paved the way for applications in catalysis, food packaging, biomedical technology and cultural heritage treatment [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%